'Costume and Fairy Tales'. Issue 2 (23rd February 2023) - Murai, Mayako
Costume plays an important part both in traditional fairy tales and in their adaptations in diverse media forms. Clothes worn by characters in fairy tales function according to the internal narrative logic that constitutes and organizes the story-world, defining and transforming the wearers' identities and social contexts. In this sense, fairy-tale clothes can be regarded as costume, defined as the kind of clothes that bears significance within a staged, performed moment for an audience. The ubiquitous persistence of fairy tales in various media intended for both children and adults renders them a means to express social, cultural and psychological anxieties evoking ethical dimensions of individual and collective struggles. As such, the way characters are embodied through their clothes bears significant narrative and performative potential in layering of meanings in performance making. While the relationship between fashion and the fairy tale has been examined in the fields of fashion studies and fairy-tale criticism, the concept of costume in the fairy tale has not yet been sufficiently explored. This Special Issue on 'Costume and Fairy Tales', with its interdisciplinary and cross-cultural approach, offers fresh insight into the fields of costume studies, fairy-tale studies, performance studies, and, more broadly, studies of art, narrative and culture across time, space and discipline.